Postcrania of the most primitive euprimate and implications for primate origins. Issue 111 (October 2017) - Boyer, Doug M.; Toussaint, Séverine; Godinot, Marc
Abstract: The fossil record of early primates is largely comprised of dentitions. While teeth can indicate phylogenetic relationships and dietary preferences, they say little about hypotheses pertaining to the positional behavior or substrate preference of the ancestral crown primate. Here we report the discovery of a talus bone of the dentally primitive fossil euprimate Donrussellia provincialis . Our comparisons and analyses indicate that this talus is more primitive than that of other euprimates. It lacks features exclusive to strepsirrhines, like a large medial tibial facet and a sloping fibular facet. It also lacks the medially positioned flexor-fibularis groove of extant haplorhines. In these respects, the talus of D. provincialis comes surprisingly close to that of the pen-tailed treeshrew, Ptilocercus lowii, and extinct plesiadapiforms for which tali are known. However, it differs from P. lowii and is more like other early euprimates in exhibiting an expanded posterior trochlear shelf and deep talar body. In overall form, the bone approximates more leaping reliant euprimates. The phylogenetically basal signal from the new fossil is confirmed with cladistic analyses of two different character matrices, which place D. provincialis as the most basal strepsirrhine when the new tarsal data are included. Interpreting our results in the context of other recent discoveries, we conclude that the lineage leading to the ancestral euprimate had already become somewhat leaping specialized, while certain specializations for the small branch niche came after crown primates began to radiate.